La nécropole de Vannes/Darioritum : données inédites sur les pratiques funéraires armoricaines dans un secteur occupé du ier au ive s. apr. J.-C. - Annaïg Le Martret; Marie Grall; Vanessa Brunet (Gallia)
The necropolis of Vannes/Darioritum (Morbihan, France) has been known since the 19th century, but it was only really explored in 2015, during a preventive excavation. As is usually the case, it is located beside a road and close to an entrance to the town. In Vannes, however, the particularity lies in the choice of a former granite quarry site with a highly fractured topography. The main basin of the quarry seems to have been used to mark the boundaries of a distinct sector of the necropolis.The exhaustive study of this funerary complex, which is exceptional within the region, took several years to complete. It sheds new light on ancient funerary practices in western Gaul, and in particular on the practices associated with cremation, since an extremely rare cremation site was discovered in the excavation area. This entity accounts for the early years of the necropolis, and anthropological and micro-morphological studies, as well as studies of the furnishings, suggest that was used long and repeatedly.In terms of burial practices in Vannes, cremation was the dominant practice during the High Empire as in Gaul as a whole, while this trend was reversed from the end of the 3rd century AD onwards, in favour of interment. At Vannes, it seems that both practices remained in use, albeit to a very limited degree, throughout the life of the necropolis. While necropolises began to be abandoned during the 3rd century AD, as urban centres contracted, this does not appear have been the case in Vannes, where several late tombs have been discovered. Thus, the practice of cremation on the site is attested as early as the 1st century AD, from the study of ceramics from the funeral pyre, and continues until the 3rd or even 4th century AD.There are 78 identified secondary cremation deposits, which include 74 secondary deposits in ossuary vessels (ceramic or glass), 3 potential secondary deposits in perishable containers and one undetermined deposit. In addition, there are several deposits of vessels that are empty or almost empty –sometimes due to their poor state of preservation– which cannot be linked to a burial site. Funerary practices remained stable, with the use of ceramic pots as ossuaries being the most common practice, as was the case in all the necropolises of regional capitals in Roman Gaul during the Early Empire. The use of glass containers (around 25%), on the other hand, is quite exceptional and makes this a benchmark of its kind. In contrast with other regions of ancient Gaul, but in line with what is usually found in the west, secondary cremation deposits mostly take the form of an isolated ossuary vessel, containing a partial and random sample of the deceased’s cremated remains. Objects accompanying the ossuary vase are rare. Of the ten confirmed burials, of which no bones have been preserved, four special cases probably consist of very young, immature individuals, who often received special treatment from the Early Empire onwards. In this sector of the necropolis there is a tile coffer, an arrangement of amphora fragments and two tombs with a nailed container from the later period.However, the anthropological study also revealed examples of very young cremated subjects, once again confirming the multiplicity of burial practices. The tombs of older subjects, which yielded accompanying furnishings, come from a period between the last quarter of the 3rd and the 4th century AD, but the cross-referencing of a burial without accompanying items with a secondary cremation deposit in an ossuary vase makes it possible to establish that this funerary practice may have occurred before the middle of the 2nd century AD. The material deposited in the later burials consists of one or two objects: one vase, two vases or one vase and a pearl necklace in one case, and the distinctive aspect of this practice lies, as in the High Empire, in the significant representation of glass vases.The spatial organisation of the burial complex does not reveal any alignment effects, but the deposits seem to have been preferentially buried in the peripheral areas, on the edge of the break in the slope that delimits the former quarry. The site’s uneven topography seems to have influenced the overall layout of the burial complex. Central empty spaces nevertheless appear and may well correspond to passages. In addition, the virtual absence of overlaps between the tombs, even when the chronological differences are significant, suggests the use of surface markers that have now disappeared. The excavation window is too short to identify the entrances to this sector of the necropolis, although the layout of the complex suggests that they were to the south, towards the current Avenue Edouard-Herriot, which probably follows the route of the road linking Vannes/Darioritum to Nantes/Condevincum.